KESENJANGAN HUKUM DALAM PENGATURAN KONTEN DIGITAL DAN KEBEBASAN BEREKSPRESI DI ERA PLATFORM MEDIA SOSIAL - Rizky Mohammad (PT. Habe Cendekia Utama, 2025)
This research aims to identify legal gaps in the ITE Law and its derivative regulations, analyze their impact on the chilling effect, the criminalization of digital expression, and the dominance of foreign platform privacy policies. It also formulates recommendations for regulatory reform that are more proportional, transparent, and in line with international human rights standards. Using a descriptive qualitative approach with a literature review, this research utilizes primary legal sources (the 1945 Constitution, Law No. 1 of 2024, Minister of Communication and Information Regulation No. 5 of 2020, Constitutional Court Decision No. 90/PUU-XXI/2023) and secondary literature from scientific articles, government reports, and recent studies on the implementation of the ITE Law on social media platforms. The results reveal unclear norms, a lack of synchronization between national regulations and global standards, excessive discretion by officials and platforms, and a lag in regulations regarding algorithms and AI, which cumulatively trigger self-censorship, increase the criminalization of criticism, and weaken digital democracy. The research recommends reformulating the multi-interpretable articles, implementing the principles of proportionality and due process of law, requiring platforms to be transparent in content moderation, and establishing a multi-stakeholder forum to ensure a democratic digital ecosystem aligned with Pancasila values in the era of national digital transformation.